2015
DOI: 10.1145/2766997
|View full text |Cite
|
Sign up to set email alerts
|

Gradient-domain path tracing

Abstract: Figure 1: Comparing gradient-domain path tracing (G-PT, L1 reconstruction) to path tracing at equal rendering time (2 hours). In this time, G-PT draws about 2,000 samples per pixel and the path tracer about 5,000. G-PT consistently outperforms path tracing, with the rare exception of some highly specular objects. Our frequency analysis explains why G-PT outperforms conventional path tracing. AbstractWe introduce gradient-domain rendering for Monte Carlo image synthesis. While previous gradient-domain Metropoli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
69
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 82 publications
(73 citation statements)
references
References 42 publications
2
69
1
1
Order By: Relevance
“…The seminal work on gradient‐domain path tracing from Kettunen et al [KMA*15] showed that gradient sampling can also lead to significant improvements for standard Monte‐Carlo path tracing. They further proposed a simpler shift mapping which only requires local path information and can be computed sequentially during the path sampling.…”
Section: Related Workmentioning
confidence: 99%
“…The seminal work on gradient‐domain path tracing from Kettunen et al [KMA*15] showed that gradient sampling can also lead to significant improvements for standard Monte‐Carlo path tracing. They further proposed a simpler shift mapping which only requires local path information and can be computed sequentially during the path sampling.…”
Section: Related Workmentioning
confidence: 99%
“…Numerous variants exist, e.g., sampling in primary space (Kelemen et al, 2002) or in path space (Veach, 1998), as well as modern extensions such as energy redistribution path tracing (ERPT, Cline et al, 2005), manifold exploration (Jakob and Marschner, 2012), half-vector space transport (Kaplanyan et al, 2014), and gradient domain methods (Kettunen et al, 2015).…”
Section: Metropolis Light Transport (Mlt)mentioning
confidence: 99%
“…One notable exception is the method introduced by Korndörfer (2011). It is also based on Voronoi partitioning, but uses a 3-D voxel grid and puts emphasis on achieving a regular quad meshing of the boundary surface.…”
Section: Revised Generation Of Synthetic Glass Shardsmentioning
confidence: 99%
See 1 more Smart Citation
“…Gradient-domain rendering approaches, e.g. [Lehtinen et al 2013;Kettunen et al 2015], sample in the gradient domain to exploit the sparsity of gradients in image space. They use finite differences of the path on the image coordinates, whereas our method uses analytical derivatives on all dimensions.…”
Section: Metropolis Light Transportmentioning
confidence: 99%